Design of wideband low-loss reconfigurable reflectarray antenna - Zhang, Xiran (Nanyang Technological University, 2024)
Reconfigurable Reflectarray Antenna (RRA) combines the advantages of traditional reflectarray antennas and phased array antennas, featuring low cost, low loss, high radiation efficiency, and high-precision beam control. It has received widespread attention in recent years. This dissertation focuses on a wideband, low-loss RRA suitable for the L-band, and conducts a simulation performance analysis of the design presented in this dissertation. A systematic investigation of beam scanning antenna technology is conducted, analyzing the characteristics of different beam scanning antenna designs. The focus is on the reconfigurable methods used in low-cost RRA designs, including a comparison of the advantages and disadvantages of different types of switches in the array, analysis of reconfigurable elements, and research on the problem of cascaded switch additive loss in current electronic RRA elements. Based on the analysis and research of RRA, a functional metasurface unit that also uses integrated PIN diodes is selected as an example to validate the simulation analysis method strategy for this dissertation’s design, and to analyze and compare the possible reasons for different simulation results. It proposes an RRA design that integrates a PIN diode with air gap. The switch of the reconfigurable unit is directly mounted on the reflective element, reducing the loss introduced by the switching device. Furthermore, this dissertation conducts a simulation and comparative analysis of the role of common metal vias in RRA design. The finding is that for designs with severe in-band resonance within the working bandwidth, appropriately oriented vertical metal vias can move the resonanceout of the working frequency band. The simulation results of the air gap replacement for the substrate scheme proposed in this dissertation are compared with the original thickened substrate scheme. It is found that the design proposed in this dissertation not only achieves better performance but also further reduces the cost of RRA units. This RRA design, integrated with PIN diodes, achieves a working bandwidth of 16% from 1.7 to 2.0 GHz, fully covering the design bandwidth requirements of the L-band, with a phase difference of 180°±10° within the working bandwidth and an insertion loss of less than 0.3 dB.